Expression of an ASCL2 related stem cell signature and IGF2 in colorectal cancer liver metastases with 11p15.5 gain. Issue 9 (17th May 2010) - Stange, D E; Engel, F; Longerich, T; Koo, B K; Koch, M; Delhomme, N; Aigner, M; Toedt, G; Schirmacher, P; Lichter, P; Weitz, J; Radlwimmer, B
Abstract : Background and aims: Liver metastases are the leading cause of death in colorectal cancer. To gain better insight into the biology of metastasis and possibly identify new therapeutic targets we systematically investigated liver-metastasis-specific molecular aberrations. Methods: Primary colorectal cancer (pCRC) and matched liver metastases (LMs) from the same patients were analysed by microarray-based comparative genomic hybridisation in 21 pairs and gene expression profiling in 18 pairs. Publicly available databases were used to confirm findings in independent datasets. Results: Chromosome aberration patterns and expression profiles of pCRC and matched LMs were strikingly similar. Unsupervised cluster analysis of genomic data showed that 20/21 pairs were more similar to each other than to any other analysed tumour. A median of only 11 aberrations per patient was found to be different between pCRC and LM, and expression of only 16 genes was overall changed upon metastasis. One region on chromosome band 11p15.5 showed a characteristic gain in LMs in 6/21 patients. This gain could be confirmed in an independent dataset of LMs (n=50). Localised within this region, the growth factor IGF2 (p=0.003) and the intestinal stem cell specific transcription factor ASCL2 (p=0.029) were found to be over-expressed in affected LM. Several ASCL2 target genes were upregulated in this subgroup of LM, including the intestinal stem cell marker OLFM4 (p=0.013). The correlation between ASCL2 expression and four known direct transcriptional targets ( LGR5, EPHB3, ETS2 and SOX9 ) could be confirmed in an independent expression dataset (n=50). Conclusions: With unprecedented resolution a striking conservation of genomic alterations was demonstrated in liver metastases, suggesting that metastasis typically occurs after the pCRC has fully matured. In addition, we characterised a subset of liver metastases with an ASCL2 -related stem-cell signature likely to affect metastatic behaviour of tumour cells.